2013
DOI: 10.1016/j.ajog.2013.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines for occupational lifting in pregnancy: evidence summary and provisional recommendations

Abstract: Empirically based lifting criteria established by the National Institute for Occupational Safety and Health (NIOSH) to reduce the risk of overexertion injuries in the general US working population were evaluated for application to pregnant workers. This report proposes criteria to guide decisions by medical providers about permissible weights for lifting tasks performed at work over the course of an uncomplicated pregnancy. Our evaluation included an extensive review of the literature linking occupational lift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
1
41
0
3
Order By: Relevance
“…Respecto al punto anterior, distintas publicaciones han establecido la necesidad de realizar intervenciones en los puestos de trabajo de embarazadas. [7][8][9][10] Los principales ejes a intervenir son: a) La presencia de factores de riesgo de Trastornos Músculo-Esqueléticos Relacionados con el Trabajo [11][12][13][14][15] ; b) Disminuir los factores de riesgo ergonómicos presentes en puestos de trabajo de embarazadas 16,17 ; c) Disminuir la carga cognitiva de los puestos y jornadas de trabajo [18][19][20][21] ; d) Controlar los factores psicosociales 21 , entre otros. Esto es sustantivo con la existencia de distintos estudios sobre intervenciones que han demostrado tener impacto en la sobrecarga física y mental de la mujer en sus puestos de trabajo.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Respecto al punto anterior, distintas publicaciones han establecido la necesidad de realizar intervenciones en los puestos de trabajo de embarazadas. [7][8][9][10] Los principales ejes a intervenir son: a) La presencia de factores de riesgo de Trastornos Músculo-Esqueléticos Relacionados con el Trabajo [11][12][13][14][15] ; b) Disminuir los factores de riesgo ergonómicos presentes en puestos de trabajo de embarazadas 16,17 ; c) Disminuir la carga cognitiva de los puestos y jornadas de trabajo [18][19][20][21] ; d) Controlar los factores psicosociales 21 , entre otros. Esto es sustantivo con la existencia de distintos estudios sobre intervenciones que han demostrado tener impacto en la sobrecarga física y mental de la mujer en sus puestos de trabajo.…”
Section: Introductionunclassified
“…Esto es sustantivo con la existencia de distintos estudios sobre intervenciones que han demostrado tener impacto en la sobrecarga física y mental de la mujer en sus puestos de trabajo. [7][8][9][10][21][22][23][24] El desarrollo de una identificación de los factores de riesgo de la salud y calidad de vida de embarazadas permite reducir una sobrecarga de la mujer, poniendo en riesgo su desarrollo tanto laboral como en su embarazo. [25][26][27][28] Por lo anterior, es necesario contextualizar desde el punto de vista del factor físico-biomecánico a que se encuentran sometidas las trabajadoras embarazadas, a través de la descripción de los mismos, determinar las dimensiones de la carga global de trabajo, presencia de factores físico-ergonómicos y la percepción de molestias músculo-esqueléticas de trabajadoras en situación de embarazo, que puedan servir de base para determinar recomendaciones iniciales que ayuden en el autocuidado de las embarazadas.…”
Section: Introductionunclassified
“…In this component, midwives will deliver health education based on the clinical guidelines for occupational lifting in pregnancy by MacDonald et al [24]. Topics for the education will include possible implications of heavy lifting during pregnancy, avoid lifting any object that weighs more Receive routine antenatal care…”
Section: Component One -Health Educationmentioning
confidence: 99%
“…Besides, there are several occupational guidelines formulated by various institutions [19,23] aimed at protecting pregnant employees against physical stress in their respective countries. More recent are the provisional clinical guidelines for occupational lifting in pregnancy by MacDonald et al [24] but none of such guidelines exist in Ghana and other LMICs. Moreover, a recent systematic review revealed that no trial has investigated the usefulness of such guidelines aimed at reducing heavy lifting among pregnant women to increase gestational age [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation